Profil Pasien Stroke di RSUD Arifin Achmad Provinsi Riau - Dimas Pramita Nugraha; Eka Bebasari; Yulia Wardani (Fakultas Kedokteran Universitas Riau, 2018)
Stroke is the first cause of death in women and the second leading cause of death in men in industrialized countries. In Asia, every year an estimated 500 thousand people experience a stroke. Therefore recognizing stroke risk factors and managing them appropriately is key to designing primary prevention strategies in non-stroke populations and secondary prevention to avoid recurrent strokes. This research was cross sectional study to describe profile stroke patients in Arifin Achmad hospital Riau Province. Research data was taken through questionnaire and patient medical records. In this study, stroke patients in Arifin Achmad Hospital were mostly <60 years old, 65.80% and male sex 64.50%. The proportion of hypertension is 90.80%. Diabetes mellitus 7.90%, dyslipidemia 63.20%, smoking 21.10%, obesity 32.90%, and sedentary life 73.70%.